COMBINED EFFECT OF GENDER AND INSTRUCTIONAL STRATEGIES ON LEARNERS’ ACADEMIC ATTAINMENT IN LITERARY APPRECIATION - Assimonye, Augusta Chiedu (Jurnal Praksis dan Dedikasi Sosial, 2024)
The study used a quasi-experimental pretest-posttest non-equivalent control group design involving intact classes assigned to experimental and control groups. Conducted in Anambra State, Nigeria, the study focused on improving Literature-in-English achievement among SSII students using the Reciprocal Peer Tutoring (RPT) strategy compared to the conventional method. A sample of 65 students (43 females, 22 males) was drawn from two co-educational schools. Data were collected using the validated and reliable 20-item Literature-in-English Achievement and Retention Test (LART). Trained teachers administered pretests, six-week lessons, posttests, and retention tests. Data were analyzed with mean, standard deviation, and ANCOVA at a 0.05 significance level. The results in Table (1) show that male students had pretest and posttest mean scores of (51.44) and (52.81) with standard deviations of (9.33) and (10.39), while female students had (50.65) and (51.47) with standard deviations of (9.68) and (10.22). The mean gain for males was (1.37) compared to females’ (0.82), indicating slightly better performance for males under the conventional method. Table (2) shows an ANCOVA result with F(1,63) = (3.564), p = (0.114) > 0.05, confirming no significant interaction effect between gender and teaching method on students’ achievement in literary appreciation. Gender did not influence posttest performance. The study concluded that the RPT strategy enhances students’ performance regardless of gender. It recommended that teachers adopt learner-centered strategies such as RPT to improve engagement and achievement in literary appreciation.